Knee pain in competitive swimming - Rodeo, S. A. (Clinics in Sports Medicine, 1999)
The high volume of training in competitive swimming results in cumulative overload injuries. Knee pain ranks second to shoulder pain as a common complaint in competitive swimmers. Most knee pain occurs on the medial side of the knee and, most commonly, in breaststroke swimmers; however, knee pain may accompany all strokes. This article reviews the incidence of knee pain, the biomechanic and anatomic factors predisposing to injury, specific injury patterns, injury diagnosis, and the treatment and prevention of injury to the knee in swimmers.